2013
DOI: 10.1007/978-3-642-41320-9_4
|View full text |Cite
|
Sign up to set email alerts
|

QRishing: The Susceptibility of Smartphone Users to QR Code Phishing Attacks

Abstract: Abstract. The matrix barcodes known as Quick Response (QR) codes are rapidly becoming pervasive in urban environments around the world. QR codes are used to represent data, such as a web address, in a compact form that can be scanned readily and parsed by consumer mobile devices. They are popular with marketers because of their ease in deployment and use. However, this technology encourages mobile users to scan unauthenticated data from posters, billboards, stickers, and more, providing a new attack vector for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 8 publications
0
48
0
5
Order By: Relevance
“…This survey contained a set of questions to identify the initiatives and the behavior of the people that scanned the QR codes. Similar to Seeburger et al [35], Vidas et al [42] found that curiosity is the main motivation for smartphone users to scan a code. Their findings highlight the need for further research on adequate tools to support the user in detecting potential threats as they are mostly scanning unverified codes because of their curiosity.…”
Section: Related User Studiesmentioning
confidence: 54%
See 4 more Smart Citations
“…This survey contained a set of questions to identify the initiatives and the behavior of the people that scanned the QR codes. Similar to Seeburger et al [35], Vidas et al [42] found that curiosity is the main motivation for smartphone users to scan a code. Their findings highlight the need for further research on adequate tools to support the user in detecting potential threats as they are mostly scanning unverified codes because of their curiosity.…”
Section: Related User Studiesmentioning
confidence: 54%
“…The importance of human-computer interaction aspects in QR code security has been acknowledged by the research of Seeburger et al [35] and Vidas et al [42]. Seeburger et al [35] investigated how users interact with QR code stickers in urban spaces with so called PlaceTagz.…”
Section: Related User Studiesmentioning
confidence: 99%
See 3 more Smart Citations